Comparison of the Investment Behavior of German and Kazakhstani Farmers: an Experimental Approach - Dulat Tubetov; Syster Christin Maart; Oliver Musshoff (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2012)
Kazakhstan and Germany have different development levels of the agricultural sectors. One of the explanations for this fact might be the different investment behavior of farmers in the two countries. We experimentally analyze whether the investment behavior of farmers is consistent with the normative benchmarks of the net present value criterion or the real options approach. Furthermore, we experimentally compare the investment behavior of farmers in the two countries in an agricultural and a non-agricultural treatment. In addition, farmers were confronted with the two treatments in a different order. Our results show that both theories cannot exactly predict the investment behavior of farmers. Farmers invest later than the net present value criterion suggests and earlier than the real options approach suggests. However, German farmers invest later than Kazakhstani farmers, which mean that the investment behavior of German farmers is more in accordance with the superior real options approach. Therefore, the different investment behavior might partly be an explanation for different development levels of the agricultural sectors of the two countries. Moreover, results are independent from the framing of an agricultural and a non-agricultural treatment. However, farmers learn from their former investment decisions and consider the value of waiting over time.
Keywords: C91; D03; D81; D92; 330; Experimental Economics; Investment Timing; Real Options; Kazakhstan; Germany